2014
DOI: 10.1111/ane.12278
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of phase III with entacapone in Parkinson's disease

Abstract: Entacapone improved daily OFF- and ON-times by a mean of 0.8 h compared with placebo across the four pooled efficacy studies and was generally well tolerated. The results of this pooled analysis potentially serve as a useful benchmarking data for new therapies (especially levodopa products) in advanced patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
6
2
Order By: Relevance
“…Entacapone significantly improved daily OFF- and ON-times as well as UPDRS II and III scores irrespective of the DDCI (carbidopa or benserazide) combined with levodopa. These results are well in line with separate reports and the overall pooled analysis of entacapone phase III studies (PSG 1997 ; Rinne et al 1998 ; Poewe et al 2002 ; Brooks and Sagar 2003 ; Kuoppamäki et al 2014 ). An important finding was also that the treatment effects of entacapone (vs placebo) did not differ between patients on LC or LB.…”
Section: Discussionsupporting
confidence: 87%
“…Entacapone significantly improved daily OFF- and ON-times as well as UPDRS II and III scores irrespective of the DDCI (carbidopa or benserazide) combined with levodopa. These results are well in line with separate reports and the overall pooled analysis of entacapone phase III studies (PSG 1997 ; Rinne et al 1998 ; Poewe et al 2002 ; Brooks and Sagar 2003 ; Kuoppamäki et al 2014 ). An important finding was also that the treatment effects of entacapone (vs placebo) did not differ between patients on LC or LB.…”
Section: Discussionsupporting
confidence: 87%
“…22,23 Based on a pooled analysis of 4 phase III entacapone trials, this increase in levodopa exposure by entacapone has translated into improved (placebo vs entacapone) daily “on/off” times at 6 months by an average of 0.8 hours. 24 Although no direct comparisons can be made, the present study with ODM-101 combinations demonstrated that increased carbidopa doses administered with levodopa and entacapone almost doubled the treatment effect on “on/off” times previously shown between entacapone and placebo. 24…”
Section: Discussioncontrasting
confidence: 41%
“…24 Although no direct comparisons can be made, the present study with ODM-101 combinations demonstrated that increased carbidopa doses administered with levodopa and entacapone almost doubled the treatment effect on “on/off” times previously shown between entacapone and placebo. 24…”
Section: Discussioncontrasting
confidence: 41%
“… 25 In a pooled analysis of published Phase III studies on 808 PD patients, entacapone showed promising results in UPDRS II ( P <0.01) and III ( P <0.01) scores. 26 A meta-analysis of 14 studies also indicated adjuvant treatment with entacapone improved UPDRS ADL and motor scores. 27 Considering the fact that entacapone can increase levodopa sustainability by extending the drug’s half-life, it was reasonable to find that LCE improved scores of UPDRS II and UPDRS III in our study, which is also consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%